Rattan furniture design: a comparison study between Malaysia and Indonesia design trend / Muhammad Muizzuddin Darus...[et.al] - Darus, Muhammad Muizzuddin; Mat Rasul, Ruwaidy; Abdul Aziz, Abu Bakar; Mat Yusof, Nurhikma; Junaidi, Deny Willy (2016)
Malaysian rattan furniture industry nowadays decline to 0% on timber export (MTIB 2016). The situation is becoming more critical with the number of skillful craftsman and rattan manufacturer declined recently. It is believes that the cost of raw material is cheaper if imported from other countries. In fact, the job of rattan seeker as economic resources are no longer famous as it was in 70s and 80s. However, Indonesian rattan still highly in demand whereby the cane tree easily can be found in Indonesian archipelago. Thus, this contributed the increment of market demand towards rattan end products. Some research shows that the Indonesia market demand was increases. Hence, make the Indonesian Rattan Industries is more reliable to the global market. Therefore, a case study has been conducted on Rattan Furniture Design between Malaysia and Indonesia rattan industries to look into design trending which is one of the factors that Malaysia Rattan Industry struggle to sustain efficiently. This paper will provide some of the comparison on rattan furniture design from both countries to analyze on how to make Malaysia Rattan Furniture Industry more relevant in the future.